О принципе сравнения для системы матричных дифференциальных уравнений - Мартынюк, А.А. (Видавничий дім "Академперіодика" НАН України, 2008)
This paper presented a comparison principle for matrix differential equations. We employ the unified Liapunov’s direct method via matrix-valued Liapunov functions and some differential inequalities.